2017
DOI: 10.1073/pnas.1712153114
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanotransmission mechanism of the MacB ABC transporter superfamily

Abstract: MacB is an ABC transporter that collaborates with the MacA adaptor protein and TolC exit duct to drive efflux of antibiotics and enterotoxin STII out of the bacterial cell. Here we present the structure of ATP-bound MacB and reveal precise molecular details of its mechanism. The MacB transmembrane domain lacks a central cavity through which substrates could be passed, but instead conveys conformational changes from one side of the membrane to the other, a process we term mechanotransmission. Comparison of ATP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
189
0
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(207 citation statements)
references
References 32 publications
6
189
0
7
Order By: Relevance
“…BceAB-type systems belong to the type VII ABC transporter superfamily, of which the Escherichia coli macrolide resistance transporter MacB is the paradigm example (22). MacB was recently shown to act according to a molecular bellows mechanism and expel its substrate from the periplasm across the outer membrane via the TolC exit duct by undergoing extensive conformational changes in its periplasmic domain (23). This mode of "transport," which does not involve physical movement of a substrate across a membrane but instead uses intracellular ATP hydrolysis to perform mechanical work in the periplasm, was termed "mechanotransmission" (23).…”
Section: Resultsmentioning
confidence: 99%
“…BceAB-type systems belong to the type VII ABC transporter superfamily, of which the Escherichia coli macrolide resistance transporter MacB is the paradigm example (22). MacB was recently shown to act according to a molecular bellows mechanism and expel its substrate from the periplasm across the outer membrane via the TolC exit duct by undergoing extensive conformational changes in its periplasmic domain (23). This mode of "transport," which does not involve physical movement of a substrate across a membrane but instead uses intracellular ATP hydrolysis to perform mechanical work in the periplasm, was termed "mechanotransmission" (23).…”
Section: Resultsmentioning
confidence: 99%
“…How MacB can protect these bacteria within host by efflux of physiological substrates bears further investigation. Recently, an electron cryomicroscopy structure of MacAB–TolC and a crystal structure of MacB were determined 30–32 . Despite this progress, many questions regarding MacAB remain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an electron cryomicroscopy structure of MacAB-TolC and a crystal structure of MacB were determined. [30][31][32] Despite this progress, many questions regarding MacAB remain. For example, the absence of a substrate-bound structure is the biggest barrier for understanding the mechanism of substrate recognition by MacB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the structure of A. actinomycetemcomitans MacB was reported and suggested to be a structural paradigm for the ABC3 transporter superfamily that includes FtsX (38). MacB was proposed to function as a mechanical pump to drive enterotoxin transport through TolC in E. coli (38). Crow et.…”
Section: Discussionmentioning
confidence: 99%
“…Crow et. al found that MacB itself did not transport enterotoxin but drove TolC to transport it instead, due to the lack of a central cavity in the MacB structure (38). As such, they proposed that MacB as a model for other “mechanotransmitters” belonging to this same ABC3 transporter superfamily.…”
Section: Discussionmentioning
confidence: 99%